Cork boiling wastewater treatment and biogas production - Gil, Luís (2013)
Cork boiling wastewater (CBW) is a very important effluent of the cork processing industry which is produced in the western Mediterranean region and western north of Africa. CBW has no utility till now constituting an environmental hazard. It is a complex liquid stream which is produced during the boiling of the cork planks. This process step is one of the key operations in cork processing. CBW is known as having suspended and dissolved solids and organic materials such as phenolic compounds being characterized by a low biodegradability and an acid pH.